Considerations of determination of economic damage amount for copyright infringement in digital environments (2015)
Technological have transformed the creation and acquisition dynamics of works in digital environments. As a result, it brings along new copyright infringement scenarios that need clear rules about how the amount of damage must be determinate when an infringement occurs. Currently in Colombia, determining the amount of damages in copyright infringement in digital environments is based on the material property theory which differs in its objective compared to the intellectual property. This article discusses the basics of the damage and now determining it in infringements of copyright in digital environments in Colombian law in contrast with the Spanish and American system in order to open a debate on the importance and the difficulties encountered in this topic.